Emerging Concepts about NAIP/NLRC4 Inflammasomes - Lage, Silvia Lucena; Longo, Carla; Branco, Laura Migliari; da Costa, Thaís Boccia; Buzzo, Carina de Lima; Bortoluci, Karina Ramalho (Frontiers in Immunology, 2014)
NAIP/NLRC4 inflammasome complexes are activated in response to proteins from virulent bacteria that reach the cell cytosol. Specific NAIP proteins bind to the agonists and then physically associate with NLRC4 to form an inflammasome complex able to recruit and activate pro-caspase-1. NAIP5 and NAIP6 sense flagellin, component of flagella from motile bacteria, whereas NAIP1 and NAIP2 detect needle and rod components from bacterial type III secretion systems (T3SS), respectively. Active caspase-1 mediates the maturation and secretion of the pro-inflammatory cytokines, IL-1β and IL-18, and is responsible for the induction of pyroptosis, a pro-inflammatory form of cell death. In addition to these well-known effector mechanisms, novel roles have been described for NAIP/NLRC4 inflammasomes, such as phagosomal maturation, activation of inducible Nitric Oxide Synthase (iNOS), regulation of autophagy, secretion of inflammatory mediators, antibody production, activation of T cells, among others. These effector mechanisms mediated by NAIP/NLRC4 inflammasomes have been extensively studied in the context of resistance of infections and the potential of their agonists has been exploited in therapeutic strategies to non-infectious pathologies, such as tumor protection. Thus, this review will discuss current knowledge about the activation of NAIP/NLRC4 inflammasomes and their effector mechanisms.